Mathematical reasoning and self-regulated learning differences by using mathematical literacy-based e-module - Rosyada, Amrina; Sari, Novita; Sukmaningthias, Novika; Nuraeni, Zuli (Universitas Hamzanwadi, 2024)
This research is motivated by the low level of students' mathematical reasoning abilities related to self-regulated learning. Several aspects that can support it include an e-module and mathematical literacy. Based on this problem, this research aims to describe students' mathematical reasoning abilities reviewed through self-regulated learning, specifically through a mathematical literacy-based e-module. The method used in this research is descriptive with a qualitative approach. The research participants were 32 8th-graders in one of the junior high schools in Palembang. Meanwhile, the research sample consisted of 4 students, consisting of 2 students with a high level of self-regulated learning and 2 students with a moderate level of self-regulated learning. Data collection techniques used were tests, questionnaires, and interviews. The research results showed that students with high levels of self-regulated learning also have a high level of mathematical reasoning ability by showing 3 out of 3 mathematical reasoning ability indicators. Meanwhile, students with moderate levels of self-regulated learning also have moderate mathematical reasoning ability, as shown by two of the 3 mathematical reasoning ability indicators.